2021
DOI: 10.1002/cam4.4088
|View full text |Cite
|
Sign up to set email alerts
|

Associations between initiating antihypertensive regimens on stage I–III colorectal cancer outcomes: A Medicare SEER cohort analysis

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…Our findings would require a larger and more diverse cohort of patients with CCB medication to draw any general conclusions. Balkrishnan et al 38 who evaluated the association between antihypertensive treatment and mortality in a cohort of 13,982 CRC patients reported a protective effect of these drugs; however, patients using CCB were not included in the analysis. Similarly, Peng et al 39 reported a beneficial impact of antihypertensives on the prognosis of 713 CRC patients, although their results were not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings would require a larger and more diverse cohort of patients with CCB medication to draw any general conclusions. Balkrishnan et al 38 who evaluated the association between antihypertensive treatment and mortality in a cohort of 13,982 CRC patients reported a protective effect of these drugs; however, patients using CCB were not included in the analysis. Similarly, Peng et al 39 reported a beneficial impact of antihypertensives on the prognosis of 713 CRC patients, although their results were not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…A detailed analysis showed a positive effect on survival of all study drug groups (ACEIs, beta blockers, diuretics), except for ARBs. Due to data availability, the analysis excluded, however, patients below 65 years old, and those using antihypertensive drugs before the diagnosis of colorectal cancer [ 32 ]. On the other hand, Holmes et al and Cardwell et al in two population studies, showed no such correlation in other groups of patients with colorectal cancer (n = 3967 and n = 4762, respectively) [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…A correlation between adherence to therapy with anti-hypertensives and decreased specific mortality due to CRC was also seen. It was therefore suggested that these drugs could be used as supplements to the anti-tumor therapy for the treatment of CRC in stages I-III [22]. In another example, Morris et al [23] evaluated patients with rectal cancer treated with neoadjuvant radiotherapy or chemo-radiotherapy followed by surgical resection and found that there was a significant positive correlation between taking ACEi/ARB anti-hypertensives and increased regression and lower tumor grade.…”
Section: Crc and Anti-hypertensivesmentioning
confidence: 99%
“…As discussed above, the use of ACEi is likely associated with a better outcome in CRC [21][22][23][24][25] but the mechanisms responsible are not fully understood and it is not yet clear whether the benefit to the patient observed in ACEi users is linked to MDSCs. ACE expression in myeloid cells is reported as a fundamental requirement for normal myelopoiesis, but ACE could also be responsible for myeloid cell modulation during the process of differentiation.…”
Section: Therapies Targeting Mdscsmentioning
confidence: 99%